A Systematic Review of The Event Organizer's E-Business - Dony Waluya Firdaus; Ghufron Ghufron; Tanti Santika (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
The purpose of this study was to conduct a systematic review of the organization of events using e-business. This study focuses on the use of technology in e-business, which is used in organizing events. The approach method used is a systematic literature review (SLR). SLR results based on indexing databases such as Google Scholar, crossref, IEEE, doaj, scimajor, and Wiley found 31 articles. Event organizers using e-business can provide offers such as planning events, organizing events, and budget planning.